Isokinetic strength of knee flexors and extensors of adolescent soccer players and its changes based on movement speed and age - Lehnert, M.; Urban, J.; Prochazka, J. H.; Psotta, R. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2011)
During childhood and adolescence there is growth in muscle strength. The dynamics of change in muscle strength and its causes have not yet been fully clarified and may differ within individuals and specific groups. The knowledge of current isokinetic strength levels among athletes of varying ages and disciplines represents important information from the point of view of sport performance, as well as health prevention. OBJECTIVE: The aim of this study is to determine within a group of highly trained adolescent soccer players (n = 45; age = 17 ± 1.2 years; body height 178.4 ± 5.3 cm, body weight 68.5 ± 7.6 kg) the isokinetic strength of knee flexors and extensors and to judge whether it is significantly influenced by age and movement speed. METHODS: A group of players was further divided according to age into 3 subgroups - U16 (n = 16); U17 (n = 14); U18 (n = 15). Unilateral strength was measured by the isokinetic dynamometer ISOMED 2000 (D. & R. Ferstl GmbH, Hemau, Germany) at angular speeds of 60° • s-1, 180° • s-1 and 360° • s-1. The parameter evaluated was the isokinetic peak torque (PT; Nm). RESULTS: The ANOVA results demonstrate that there was a significant decrease in the PT within the entire group of players with an increase in speed during both flexion and extension (dominant extremity: p < 0.001 resp. p < 0.019; non-dominant extremity: p < 0.001; resp. p < 0.001). The difference in PT among the age categories was not significant for both flexors and extensors at the speed of 60° · s-1 (p = 0.005; resp. p = 0.036) and the speed of 180° · s-1 (p = 0.036; resp. p = 0.033). However, significant differences in PT among individual categories were confirmed only in some cases and, by contrast, an insignificant decrease was marked with nondominant leg extensors. CONCLUSIONS: The results of this study indicated the state of the strength readiness of the highly trained soccer players in the junior category and the potential shortcomings in the concept of strength preparation within a leading club in the Czech Republic. These results contributed to the deepening of knowledge about changes in strength with age and confirmed the importance of applying diagnostics during systematic long-term sport preparation.